Mujeres en la imaginación Colectiva Una historia de discriminación y resistencia - FERNANDEZ, Ana María (PAIDOS, 1992)
Contenido: Bellucci,M.; Burin,M.; Corsi,J.; Chejeter,S.; Dio-Bleichmar,E.; Feijóo,M.C.; Giberti,E.; Hercovich,Etc.